Integrasi Fitur Detailed Performance Dalam Membangun Website Resource Monitoring Server Untuk Pt Neural Technologies Indonesia - Ridho Sentana, Ahmad; Iqbal, Muhammad; Tra Doni Ginting, Edi (eProceedings of Applied Science, 2024)
PT Neural Technologies Indonesiaprovides IT solutions for various industries, includingtelecommunications, healthcare, and mining. Efficiencyserver management is critical for serviceservices, so this project aims to build an integratedintegrated server monitoring dashboard system. This systemcollects data from multiple servers, stores it inin InfluxDB, and visualizes it on a dashboard.The project methodology includes a literature study, integration ofProxmox hypervisor with InfluxDB, implementation ofdata processing, and testing and evaluation toensure system functionality and performance. Project resultsinclude server data processing, integration withdatabases and agents, and features such as time-range filters,update interval, CPU utilization summary, and summary of theTop 5 High Hosts. This system improves the efficiency ofmonitoring and management of servers, as well as improvingsecurity and stability of the company's IT infrastructure. Keywords: server monitoring, Integration, data processing